Sleep deprivation induces delayed regeneration of olfactory sensory neurons following injury - Han, Bing; Kikuta, Shu; Kamogashira, Teru; Kondo, Kenji; Yamasoba, Tatsuya (Frontiers in Neuroscience, 2022)
The circadian system, which is essential for the alignment of sleep/wake cycles, modulates adult neurogenesis. The olfactory epithelium (OE) has the ability to generate new neurons throughout life. Loss of olfactory sensory neurons (OSNs) as a result of injury to the OE triggers the generation of new OSNs, which are incorporated into olfactory circuits to restore olfactory sensory perception. This regenerative potential means that it is likely that the OE is substantially affected by sleep deprivation (SD), although how this may occur remains unclear. The aim of this study is to address how SD affects the process of OSN regeneration following OE injury. Mice were subjected to SD for 2 weeks, which induced changes in circadian activity. This condition resulted in decreased activity during the night-time and increased activity during the daytime, and induced no histological changes in the OE. However, when subjected to SD during the regeneration process after OE injury, a significant decrease in the number of mature OSNs in the dorsomedial area of the OE, which is the only area containing neurons expressing NQO1 (quinone dehydrogenase 1), was observed compared to the NQO1-negative OE. Furthermore, a significant decrease in proliferating basal cells was observed in the NQO1-positive OE compared to the NQO1-negative OE, but no increase in apoptotic OSNs was observed. These results indicate that SD accompanied by disturbed circadian activity could induce structurally negative effects on OSN regeneration, preferentially in the dorsomedial area of the OE, and that this area-specific regeneration delay might involve the biological activity of NQO1.